Association of Alfven waves and proton cyclotron waves with electrostatic bipolar pulses: magnetic hole events observed by Polar - Lakhina, G. S.; Tsurutani, B. T.; Pickettd, J. (My University, 2004)
Two magnetic hole events observed by Polar on 20 May 1996 when it was in the polar cap/polar cusp boundary layer are studied. Low-frequency waves, consisting of nonlinear AlfvÃ©n waves and large amplitude (Â±14nT peak-to-peak) obliquely propagating proton cyclotron waves (with frequency f~0.6 to 0.7 fcp), accompanied by electric bipolar pulses (electron holes) and electron heating have been observed located within magnetic holes. It is shown that low-frequency waves can provide free energy to drive some high frequency instabilities which saturate by trapping electrons, thus, leading to the generation of electron holes.
Keywords: Magnetic holes; Alfven waves; Proton cyclotron waves